Cross-Generational Communication in Public Service Delivery - Usman, Rahmalia; Sazali, Hasan; Djamil, Munawar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
Intergenerational interaction is an increasingly important factor shaping the functioning and adaptability of public organizations. In bureaucratic environments, these interactions become more complex due to differences in values, authority orientations, work styles, and technological familiarity across generations. While prior research has largely focused on generational dynamics in private-sector organizations, limited empirical evidence explains how these dynamics operate within public bureaucracies in Aceh Province, where hierarchical norms and administrative cultures differ significantly. This study examines how intergenerational interaction is constructed within the Pidie District Government and how it influences organizational effectiveness and public service delivery. Using a qualitative descriptive approach, data were collected through interviews, participant observations, and analysis of internal regulations across several government agencies. The findings reveal three dominant patterns: technological competency gaps that disrupt task coordination, varying interpretations of bureaucratic hierarchy that affect communication flow, and contrasting work-style orientations that shape teamwork and conflict emergence. These patterns often lead to recurring misunderstandings and reduced workflow efficiency. However, adaptive leadership, structured knowledge-sharing routines, and informal mentoring between generations were found to effectively minimize barriers. The study contributes to public administration literature by highlighting how generational identities intersect with bureaucratic norms. Practically, the results emphasize the need for targeted digital literacy initiatives, clearer internal communication guidelines, and institutionalized cross-generational mentoring to enhance organizational cohesion and improve service delivery.